Comparative repartition of 226Ra, 238U, 234U, 230Th and 232Th in a variety of soils sampled from geological formations in the NE of the Basin of Paris. (September 2017) - Pourcelot, L.; Calmon, Ph; Chabaux, F.; Conil, S.; Galy, C.; Granet, M.; Lascar, E.; Leclerc, E.; Perrone, T.; Redon, P.O.; Rihs, S.
Highlights: U, 234 U, 230 Th and 226 Ra were determined in soils sampled on geological formations from the NE of the Basin of Paris. Ra is correlated with the finest soil fraction (<2 µm), suggesting this latter is involved in the retention of radium. The enrichment of soils in 226 Ra compared to 238 U and 230 Th is associated with mica-like mineral, i.e. illite-smectite. Unlike soils, litters exhibit 226 Ra depletion compared to both 238 U and 230 Th which remains poorly explained up to now. The retention of radium in the soil and/or degradation process of the litter are assumed to explain litters signatures.